TVT-S for surgical treatment of stress urinary incontinence: prospective trial, 1-year follow-up - Krofta, Ladislav; Feyereisl, Jaroslav; Velebil, Petr; Otcenásek, Michal; Kasíková, Eva; Krcmár, Michal (International urogynecology journal, 2010)
INTRODUCTION AND HYPOTHESIS: The aim of this study was to evaluate the effectiveness of and morbidity associated with the tension-free vaginal tape-secur (TVT-S) procedure in women with stress urinary incontinence (SUI). METHODS: We performed a prospective trial, examining 86 women with primary SUI. Eighty-two patients had a 1-year follow-up (dropout rate = 4.6%). The preoperative evaluation included urinalysis, urodynamic studies, and validated questionnaires. The 1-year outcome evaluation also included a 1-h pad testing. RESULTS: At the 1-year follow-up, 43 (52.4%) women were objectively cured, and 14 (17.1%) women were objectively improved. Subjectively, 49 (59.7%) patients did not experience urine loss, and 18 (22.2%) women improved in this respect. Postoperative de novo urge incontinence symptoms developed in 24.4% (n = 20) of patients. Vaginal defect healing occurred in 6.1% (n = 5) of patients, and one (1.2%) case of urethral erosion was reported. CONCLUSION: Objective and subjective cure rates following TVT-S are inferior to other tape procedures.
Keywords: urologické chirurgické výkony; lidé středního věku; následné studie; Middle Aged; ženské pohlaví; prospektivní studie; suburetrální pásky; Follow-Up Studies; Time Factors; Urologic Surgical Procedures; časové faktory; Female; lidé; Humans; Prospective Studies; Suburethral Slings; Urinary Incontinence, Stress; stresová inkontinence moči